Exploring the expression of defence-related genes in Actinidia spp. after infection with Pseudomonas syringae pv. actinidiae and pv. actinidifoliorum: first steps - Silva, M. Nunes da (2019)
Kiwifruit bacterial canker (KBC), caused by Pseudomonas syringae pv. actinidiae (PSA), is currently the most destructive disease of kiwifruit worldwide. Conversely, a closely related bacterial strain, P. syringae pv. actinidifoliorum (PFM), only causes necrotic spots and has not been associated with plant mortality. Moreover, there is some evidence on the higher susceptibility of the Actinidia chinensis var. deliciosa kiwifruit species to KBC, compared with A. arguta, but the reasons behind it are still largely unknown. In this work, micropropagated plants of Actinidia chinensis var. deliciosa 'Hayward' and A. arguta var. arguta 'Ken's Red' were inoculated with PSA or with PFM (10(7) CFUs mL(-1)). Disease development was monitored 1, 2 and 5 days post inoculation (dpi) through the determination colony forming units (CFUs) and the expression analysis of six plant defence-related genes (APX, CAT, SOD, LOX1, SAM and TLP1). At 5 dpi, CFUs in plant tissues inoculated with PSA and PFM were, respectively, 17.4-fold and 2.8-fold higher in A. chinensis compared with A. arguta. Expression of antioxidant enzyme-related genes was very distinct between the two kiwifruit species: SOD expression was drastically increased in A. chinensis (up to 2.1-fold, 5 dpi), whereas in A. arguta CAT was the most upregulated gene (up to 1.7-fold, 2 dpi). LOX1, involved in jasmonic acid biosynthesis, was upregulated in both species, however reaching the highest values at 2 dpi in A. chinensis (2.2 fold) and 1 dpi in A. arguta (1.9-fold). It is concluded that A. arguta is much more tolerant to PSA than A. chinensis and that the molecular mechanisms between the two kiwifruit species involve specific defence pathways being triggered at distinct moments after plant infection.